Optimization of industrial matching grant application system in ump : a value stream mapping approach - Laili, Zulkepeli (2022)
Value Stream Mapping is a lean practice that used for continuous performance. It is a method or technique that provide an improvement in lead time, processing time, productivity, quality, profitability and customer satisfaction through waste elimination. There are many similar techniques under lean management strategies such as Kanban System, Total Productive Maintenance and Pull System. In this study, we will be looking at how the process of UMP Industrial Matching Grant can be optimized through the use of Value Stream Mapping Approach. We would like to know whether the performance of this grant can be improved and the lead time and processing time is been shorter. Also, we would also find out whether the customer satisfaction is improved while the performance of the grant is at the level best. Value Stream Mapping approach is also known as material or information flow mapping is famous for specific process and easily quantifies duration and capacity produced at each process. The mapping includes both material and information flows and is starts from the beginning of the process until it reaches the customer. The main purpose of the Value Stream Mapping approach is to recognize and removing waste in the mapping which will provide more efficiency to the value stream. When the waste is been removed, the productivity increased and quality is improving. In Value Stream Mapping approach, for privatization bodies, they enforcing Lean Management Strategy mainly to increase profit. But before that happens, they start with identification of waste. The profit is been generated and keep increased by the elimination of waste. Value Stream Mapping approach can be practiced in every business and process since it provides contribution from entire organization. In this study, we will focus on the processes in the Grant Management System and whether or not the process can be optimized with the waste withdrawal and minimum lead time in between the processes.